Planning for sustainable food communities: An optimal spatial allocation study of food hubs considering the 15-min city concept—The case of LebensMittelPunkte in Berlin - Klebl, Fabian; Walthall, Beatrice; Vicente-Vicente, José Luis (Frontiers in Sustainable Food Systems, 2022)
Food hubs (FHs) providing neighborhoods with regional food from agroecological production are a promising concept for a sustainable food system transformation. However, their operationalization and scaling are still unclear. We developed a methodological approach that, for the first time, scales out FHs to an entire city (Berlin) based on a 15-minute walking distance and socio-culturally oriented sub-districts as underlying spatial units. We considered the population density and the distance to organic groceries, public transportation and between FHs to estimate their most suitable locations. The results reveal an optimal allocation of 231 FHs covering 91 % of the city’s populated areas in a radius lower than 1 km and almost the entire city within a 1.5 km radius. We found this approach to be a meaningful way to plan the inner-city allocation of FHs from an integrative perspective and to adopt urban policies by considering the local specificities of each neighbourhood. The scaling out of FHs in Berlin allows for the creation of a sustainable city-region food system that increases the resilience of the metropolitan food environment. We generally propose a participative and integrative approach in order to realize this process.